2016
DOI: 10.5433/1679-0359.2016v37n3p1219
|View full text |Cite
|
Sign up to set email alerts
|

High gamma irradiation doses and long storage times reduce soybean seed quality

Abstract: High quality seeds are required for soybean production. This study evaluated the effect of gamma irradiation and storage time on seed quality in soybean lines VX04-6828 and VX04-5692. Seeds were gamma irradiated ( 60 Co) with 0, 50, 150, and 250 Gy. After the first seed production cycle (M1), the harvested seeds were stored in the laboratory for 0, 2, 4, and 6 months. Moisture content, seed quality (germination rate, dead seeds, and normal and abnormal seedlings), and seed vigor (first germination count, germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
0
1
Order By: Relevance
“…For abnormality of seedlings and dead seeds, responses of possible mutations observed by the soybean lines were evident and when they presented similar behaviors in the M2 generation for the different doses evaluated. These results can be elucidated by the radiosensitivity of soybean seeds to plant segregation after cultivation and at doses greater than 150 Gy, which results in modified plants that produce seeds of low physiological quality (Nobre et al, 2016). In the present study, however, the characteristics set for the M2 generation showed low percentages of abnormal seedlings and dead seeds.…”
Section: Discussioncontrasting
confidence: 49%
“…For abnormality of seedlings and dead seeds, responses of possible mutations observed by the soybean lines were evident and when they presented similar behaviors in the M2 generation for the different doses evaluated. These results can be elucidated by the radiosensitivity of soybean seeds to plant segregation after cultivation and at doses greater than 150 Gy, which results in modified plants that produce seeds of low physiological quality (Nobre et al, 2016). In the present study, however, the characteristics set for the M2 generation showed low percentages of abnormal seedlings and dead seeds.…”
Section: Discussioncontrasting
confidence: 49%